Total Anomalous Pulmonary Venous Connection (TAPVC) (Supra cardiac type) - A Case Study - Hassan, MK; Hasan, KA; Ahmed, F; Rahim, A; Quader, SA; Ullah, M; Khan, JH; Salam, A; Mahmood, KN (Cardiovascular Journal, 2010)
Repair of Total Pulmonary venous connection (TAPVC) continues to be associated to significant mortality and morbidity.We here reported a female patient of two and half years, underwent rechanneling of supracardiac TAPVC, diagnosis was suggested by Echocardiography and confirmed by catheter-angiography which allowed definition of the anatomy. The patient has got fluent pulmonary venous drainage and her heart function resumed to NYHA I. TAPVC should be operated on immediately at definite diagnosis, the fluency of common pulmonary vein-left atrium anastomosis and proper post operative care can ensure a satisfactory outcome. Key words: Total anomalous pulmonary venous connection (TAPVC); Pulmonary artery hypertension. DOI: 10.3329/cardio.v3i1.6437 Cardiovasc. j. 2010; 3(1): 104-106